A utilização de lipases imobilizadas em reações de esterificação em meio não aquoso - Leite, Marcelo Teixeira (1999)
The purpose of this work was to study the performance of two lipases, Lipozyme and Novozym 435, in lipase-catalyzed esterifications in nonaqueous medium. The focus of this study was the enzimatic synthesis of n-butyl oleate. A pervaporation reactor was set up to carry out the reactions. Pervaporation selectively removes water from the reaction mixture using a nonporous polymeric membrane, cellulose acetate. Conversions were determined by the cupric acetate method. In the synthesis of n-butyl oleate catalized by Lipozyme, the lipase activity decreased with an increase in the reaction temperature. Maximum activity was achieved at 30°C. At 60°C the activity was minimal. The decrease in reaction mixture viscosity by addition of a solvent caused a great increase in conversion. On the other hand, increments on the amount of enzime used in the reaction mixture did not affect the formation of products. In the synthesis of n-butyl oleare using Novozym 435, the enzimatic activity was the same in the range between 30°C-60°C. The conversion was directly proportional to the amount of enzyme until the limit of 10% (m/m) on oleic acid. Changes on the viscosity and amount of butanol did not affect the reaction productivity